2000
DOI: 10.1053/euhj.2000.2242
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of balloon angioplasty versus rotational atherectomy in complex coronary lesions (COBRA study)

Abstract: Complex coronary artery lesions can be treated with a high level of success and low complication rates either by PTCA with adjunctive stenting or rotablation. The long-term clinical and angiographic outcome is comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(52 citation statements)
references
References 19 publications
2
42
0
8
Order By: Relevance
“…TLR was performed more frequently in the RA group (42.4%) and the EL group (46.0%) than in the BA group (31.9%, p = 0.013) [18]. In the COBRA trial, 502 patients were enrolled and similar results were achieved [19]. The procedural success was achieved in 78% of individuals from the PCI group, and in 85% of the RA group (p = 0.038).…”
Section: Discussionsupporting
confidence: 48%
“…TLR was performed more frequently in the RA group (42.4%) and the EL group (46.0%) than in the BA group (31.9%, p = 0.013) [18]. In the COBRA trial, 502 patients were enrolled and similar results were achieved [19]. The procedural success was achieved in 78% of individuals from the PCI group, and in 85% of the RA group (p = 0.038).…”
Section: Discussionsupporting
confidence: 48%
“…17, 18 When treatment is required for heavily calcified lesions, however, RA remains an important tool for preventing insufficient expansion, asymmetric expansion, or stent malapposition, and improves procedure success rates. 19 In addition, balloon angioplasty alone requires high-pressure dilatation, increasing the risks of coronary dissection and thrombosis when treating a heavily calcified lesion. Higher rates of complications have been noted with the use of atherectomy devices during PCI.…”
Section: Discussionmentioning
confidence: 99%
“…In the ARTIST trial comparing RA + balloon angioplasty to balloon angioplasty alone, the primary endpoint was the change in minimum lumen diameter after 6 months, and the net change was significantly smaller in the RA group (0.45 ± 0.57 vs 0.67 ± 0.54 mm, p = 0.0019) [47]. One component of the primary endpoint was not met in the COBRA trial, a randomized study of RA and balloon angioplasty, as the rate of restenosis at 6 months was similar in both groups (48.9 vs 51.1%, p = 0.333) [43]. In the randomized ERBAC trial, comparing balloon angioplasty, excimer laser angioplasty and RA, the RA patients had a significantly higher rate of the primary endpoint of procedural success (diameter stenosis <50%, absence of death, Q-wave MI or CABG); however, the authors concluded that RA did not result in better late outcomes [44].…”
Section: Rotational Atherectomymentioning
confidence: 99%
“…In cases where lesions cannot be crossed or dilated, RA can result in greater acute gain and improvements in overall procedural success [41]. However, improvements to mid and long-term clinical outcomes have not been consistently demonstrated [42][43][44].…”
Section: Rotational Atherectomymentioning
confidence: 99%
See 1 more Smart Citation